IMPLEMENTASI QRIS SEBAGAI STRATEGI PEMASARAN UMKM DALAM MENARIK KONSUMEN GEN Z DI BALAI BUNTAR - Tono, Supratman; Prasesa, Bela Julia; frasetyo, frasetyo; Harapan, Putri Mayang Sari; Aulia, Alifa Qezi; Ivanov, Alin (Student Journal of Business and Management, 2026)
This study aims to analyze the effect of perceived ease of use, digital promotion attributes, and perceived trust on the purchase decisions of Generation Z consumers using QRIS at micro, small, and medium enterprises (MSMEs) in the Balai Buntar area. A quantitative approach was employed using multiple linear regression analysis on 100 respondents. The findings reveal that perceived ease of use and perceived trust have a positive and significant effect on purchase decisions, while digital promotion attributes do not show a significant impact. Simultaneously, the three variables account for 53.5% of the variation in purchase decisions. This study confirms that trust is the most dominant factor driving Generation Z to transact using QRIS at local MSMEs. Keywords: digital promotion attributes; ease of use; Generation Z; purchase decision; QRIS